Religious accommodation and its limits - Raza, Farrah (Oxford London New York New Delhi Sydney Hart, 2023)
"When does religious accommodation undermine the autonomy of others? On what grounds should religious accommodation claims be limited? This book offers an original model of religious accommodation which can be applied in practice in secular liberal democracies where religious diversity continues to pose various challenges. Firstly, the book makes a case for religious accommodation by addressing the key normative challenges raised by religious claims. Secondly, it offers a typology of how religious claims can be managed and limited through the careful balancing of competing interests. The author draws on case study examples from jurisdictions subject to the European Court of Human Rights and the European Union's Court of Justice such as the UK, Germany and France. The result is a timely contribution to the debate on how a legal duty or policy approach in favour of religious accommodation can be applied in practice. Moreover, the proposed model offers criteria that can be used to guide the implementation of equality policies in contexts such as employment and education. The book will be of interest to academics, legal practitioners and policy-makers."--
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Religious Tolerance -- European Union countries; Civil Rights -- Religious aspects -- European Union countries; Religion And Politics -- European Union countries; Hochschulschrift